1997
DOI: 10.1111/j.1440-1827.1997.tb03733.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanocytoma of the foramen magnum

Abstract: This report concerns a 66-year-old man with a melanocytoma arising at the foramen magnum. Magnetic resonance imaging disclosed a well-circumscribed tumor extending from the medulla oblongata to C1 with gadolinium enhancement. A heavily pigmented tumor located under the leptomeninges was removed surgically. Although the patient died 8 months later of renal cell carcinoma, no recurrence or metastasis of the melanocytoma was detected by radiographic examination. Microscopically, the resected tumor was composed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Although PCPAM and primary malignant melanomas of the leptomeninges originate from leptomeningeal melanocytes, they are different in appearance and behavior 14,15,16,17,18,19. PCPAMs have a much better prognosis than their malignant counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Although PCPAM and primary malignant melanomas of the leptomeninges originate from leptomeningeal melanocytes, they are different in appearance and behavior 14,15,16,17,18,19. PCPAMs have a much better prognosis than their malignant counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…20 Our review of the literature revealed 35 cases of intracranial meningeal melanocytomas. [1][2][3][4][5][6][7][8][9][10][11][12][13][15][16][17][18][19][22][23][24][25][26][28][29][30][31][32][33] Of these 35 tumors, 18 were supratentorial and half of these occurred in Meckel cave ( Table 1). The locations of the other supratentorial melanocytomas also tended to be at or near the cranial base, including the sphenoid wing, 19 cavernous sinus, 7 temporal convexity, 23 occipital tentorial surface, 10,13 and frontal region.…”
Section: Discussionmentioning
confidence: 99%
“…27 Postoperative survival time in patients harboring intracranial meningeal melanocytomas has ranged from 1 to 28 years. [1][2][3][4][5][7][8][9][10][11][12][13]16,[18][19][22][23][24][25][26][28][29][30][31][32][33] …”
Section: J Neurosurg / Volume 94 / May 2001mentioning
confidence: 99%
See 1 more Smart Citation
“…Meningeal melanocytomas occur at every age, are usually unilocular and appear as nodes attached to the dura mater. They are mainly located in the posterior cranial fossa or the spinal canal (4,11). Imaging studies of these tumors show homogeneous contrast enhancement (12).…”
Section: Discussionmentioning
confidence: 99%